Mapping the gene causing X-linked recessive idiopathic hypoparathyroidism to Xq26-Xq27 by linkage studies. - Thakker, R; Davies, K; Whyte, M; Wooding, C; O'Riordan, J (1990)
Idiopathic hypoparathyroidism has been reported to occur as an X-linked recessive disorder in two multigeneration kindreds. Affected individuals, who are males, suffer from infantile onset of epilepsy and hypocalcemia, which appears to be due to an isolated congenital defect of parathyroid gland development; females are not affected and are normocalcemic. We have performed linkage studies in these two kindreds (5 affected males, 11 obligate carrier females, and 44 unaffected members) and have used cloned human X chromosome sequences identifying restriction fragment length polymorphisms to localize the mutant gene causing this disorder. Our studies established linkage between the X-linked recessive idiopathic hypoparathyroid gene (HPT) and the DXS98 (4D.8) locus, peak LOD score = 3.82 (theta = 0.05), thereby mapping HPT to the distal long arm of the X chromosome (Xq26-Xq27). Multilocus analysis indicated that HPT is proximal to the DXS98 (4D.8) locus but distal to the F9 (Factor IX) locus, thereby revealing bridging markers for the disease. The results of this study will improve genetic counseling of affected families, and further characterization of this gene locus will open the way for elucidating the factors controlling the development and activity of the parathyroid glands.